LIMIT VALUES AS AN UNIVERSAL METHOD OF DESCRIPTION OF PHYSICAL REALITY - Bolotin, Yu. L.; Cherkaskiy, V. A.; Yanovsky, V. V. (Одеські астрономічні публікації, 2017)
There are two main forms of cognition of Nature: empiric knowledge obtained from the experience, and theory as system of ideas and principles. Each of the two forms uses its own methods. While empirics or phenomenology is based on experiments, theory mostly deals with axiomatic approach. Every axiomatics starts from the principal question: what statements should be chosen as axioms? The present work uses the existence of limit values as the initial axiom. It is well known that the statement about the existence of minimum quantum of action ħ is sufficient to build all the Quantum Mechanics, likewise maxi-mum velocity value c—for the Special Relativity. Similar approach can be realized in General Relativity as well, which can be built on the postulated existence of limit (maximum) power = c5 / 4G It seems natural in context of this axiomatics to transit from the traditional Planck’s units to the modified ones, i.e. from the set (ħ, c, G) to (ħ, c, ), with the latter containing exclusively limit values. The approach considered in the present paper opens new exciting possibilities for interpretation of the known results and obtaining the new ones.